PENGARUH BUDAYA KREATIF, MOTIVASI INTRINSIK, DAN KEPEMIMPINAN BIROKRATIK TERHADAP KINERJA ORGANISASI BERBASIS BALANCED SCORECARD DAN DAMPAKNYA PADA KEUNGGULAN BERSAING - Wardati Arfani; Iwan Hermawan (JEM Jurnal Ekonomi dan Manajemen, 2018)
The purpose of this research is to know the influence of creative culture, intrinsic motivation, leadership and bureaucratic with a performance-based organization against the balanced scorecard and its impact on competitive advantage in the Marine and Fisheries Agency of Bangka district The middle. either partially or simultaneously. The methods used in this research is quantitative methods, qualitative descriptive analysis supported, so that in this study the author will prove a hypothesis has been formulated before and make the analysis calculation based on existing data as well as described in a systematic, factual and accurate regarding the facts, properties, and relationships between phenomena examined. Data obtained from the dissemination of the questionnaire as many as 61the respondents as well as population research. Questionnaire data are then tested with the analysis of Partial Least Square (PLS). The research States that the Creative Culture has a partial influence on performance BSC intrinsic motivation has a partial influence on the performance of the BSC. The leadership of bureaucratic with has a partial influence on the performance of the BSC. The performance of the BSC has partially influence against the competitive advantage. Creative Culture, intrinsic motivation, and bureaucratic with Leadership simultaneously had a significant influence on the performance of the BSC.